PENGAWASAN DALAM PENYELENGGARAAN PENDIDIKAN ANAK USIA DINI (PAUD) DESA DI KECAMATAN BENGKALIS KABUPATEN BENGKALIS (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractEarly childhood education management achievement determines the quality of education services to the kids who they are in the golden age as crucial times in their life, influencing of their next level education process. The aim of this research is to find out the achievement of early childhood education management in Bengkalis district. The research sub-focuses are: 1) curriculum arrangement and application, 2) the human resources utilization, 3) facilities utilization, 4) financial management, and 5) institution network.This is a descriptive qualitative research, located at PAUD Kasih Bunda of Teluk Latak village and PAUD Cahaya Insan Penebal village of Bengkalis district. The data was gained through interview, observation, and document analizing. The informans are manegers, teachers, society man, parents, and nonformal early childhood education controller of Bengkalis district. Then, the collecting data was analized by interpretative approach.The results of this study shows that the curriculum management and application at both PAUD Kasih Bunda and PAUD Cahaya Insan could be categorized good, eventhough parents donât get contribution in teaching material development. Human resources which consist of the manegers, teachers of both early childhood education institutions are not categorized as academic standard provided. Then, both institutions of early childhood education has equiped faciclities for learning process, but it concerns to the lack of safety, not confortable, and healthy standard for the kids. Administration staff is not profesional yet, so that the financial management is not accuntable and transparancy. And the last found of both institutions have networking to somes small authorities in the villages without programs and written commitments.KeyWords: Early Childhood Education, Controlling